Research Progress in the Application of Exosomes in Immunotherapy - Zhang, Xiaofang; Xu, Donggang; Song, Yingqiu; He, Rong; Wang, Tianlu (Frontiers in Immunology, 2022)
Exosomes are nanoscale extracellular vesicles (EVs), which are present in all body fluids tested. They are secreted by a variety of cells including macrophages, dendritic cells, mast cells, granulocytes, lymphocytes, and tumor cells. Exosomes secreted by different cells have different biological components and functional characteristics and play an important role in many pathophysiological activities. Recent studies have revealed that exosomes can regulate the occurrence and development of inflammatory immune diseases and tumors by transmitting their unique proteins, lipids, and nucleic acids as signaling molecules to other cells. Exosomes serve as a novel class of diagnostic biomarkers and drug delivery systems with promising applications in immunotherapy, particularly because breakthroughs in nanotechnology have led to the development and exploration of engineered exosomes for immunotargeted therapies. Therefore, here we review the progress being made on the application of exosomes in immunotherapy and its multiple regulatory mechanisms and explore the potential application of exosomes in immunotherapy in the future.